RETRACTED: The efficacy and adverse effects of anlotinib in the treatment of high-grade glioma: A retrospective analysis - Shen, Fangcheng; Li, Jing; Liu, Feng; Sun, Ni; Qiu, XiangNan; Ding, Wei; Sun, XiangDong (Frontiers in Oncology, 2023)
Introduction Anlotinib, a novel multi-kinase inhibitor, was found to improve progression-free survival (PFS) in brain metastases. Methods This paper retrospectively analyzed 26 newly diagnosed or recurrent high-grade gliomas from 2017 to 2022, and the patients received oral anlotinib during concurrent postoperative chemoradiotherapy or after recurrence. Efficacy was evaluated according to the Response Assessment in Neuro-Oncology (RANO) criteria, and the main study endpoints were PFS at 6 months and overall survival (OS) at 1 year. Results After the follow-up, until May 2022, 13 patients survived and 13 patients died, with a median follow-up time of 25.6 months. The disease control rate (DCR) was 96.2% (25/26), and the overall response rate (ORR) rate was 73.1% (19/26). The median PFS after oral anlotinib was 8.9 months (0.8–15.1), and the PFS at 6 months was 72.5%. The median OS after oral anlotinib was 12 months (1.6–24.4), and the OS at 12 months was 42.6%. Anlotinib-related toxicities were observed in 11 patients, mostly grades 1–2. In the multivariate analysis, patients with Karnofsky Performance Scale (KPS) above 80 had a highermedian PFS of 9.9months (p = 0.02), and their sex, age, IDH mutation, MGMTmethylation, and whether anlotinib was combined with chemoradiotherapy or maintenance treatment had no effect on PFS. Conclusion We found that anlotinib combined with chemoradiotherapy in treating high-grade central nervous system (CNS) tumors can prolong PFS and OS and that it was safe.